2015
DOI: 10.1128/aac.00944-15
|View full text |Cite
|
Sign up to set email alerts
|

IncA/C Plasmid Carrying bla NDM-1 , bla CMY-16 , and fosA3 in a Salmonella enterica Serovar Corvallis Strain Isolated from a Migratory Wild Bird in Germany

Abstract: A Salmonella enterica serovar Corvallis strain was isolated from a wild bird in Germany. This strain carried the IncA/C 2 pRH-1238 plasmid. Complete sequencing of the plasmid was performed, identifying the bla NDM-1 , bla CMY-16 , fosA3, sul1, sul2, strA, strB, aac(6=)-Ib, aadA5, aphA6, tetA(A), mphA, floR, dfrA7, and merA genes, which confer clinically relevant resistance to most of the antimicrobial classes, including ␤-lactams with carbapenems, fosfomycin, aminoglycosides, co-trimoxazole, tetracyclines, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 17 publications
3
58
0
2
Order By: Relevance
“…On both of our IncB/O plasmids and C629 plasmid unnamed1 there was a remnant (131 bp) of ISAba125 upstream of bla NDM , confirming the hypothesis that ISAba125 is closely linked with the original mobilization of bla NDM (17). Although genes fosA3 and bla NDM-1 on the same plasmid were found in Salmonella from a migratory wild bird in Germany (18), fosA3 was located ϳ73 kb away from bla NDM-1 in that plasmid. The annotation and blast results in our study revealed a novel gene arrangement and that the new fosA3-bla NDM-9 resistance region might be developed by acquiring a resistant gene through stepwise integration and/or recombination events mediated by IS26 and ISAba125.…”
Section: Table 1 Characterization Of Mcr-1-positive Isolates and Theisupporting
confidence: 78%
“…On both of our IncB/O plasmids and C629 plasmid unnamed1 there was a remnant (131 bp) of ISAba125 upstream of bla NDM , confirming the hypothesis that ISAba125 is closely linked with the original mobilization of bla NDM (17). Although genes fosA3 and bla NDM-1 on the same plasmid were found in Salmonella from a migratory wild bird in Germany (18), fosA3 was located ϳ73 kb away from bla NDM-1 in that plasmid. The annotation and blast results in our study revealed a novel gene arrangement and that the new fosA3-bla NDM-9 resistance region might be developed by acquiring a resistant gene through stepwise integration and/or recombination events mediated by IS26 and ISAba125.…”
Section: Table 1 Characterization Of Mcr-1-positive Isolates and Theisupporting
confidence: 78%
“…ST1 is strongly associated with the carriage of bla NDM (15/20 plasmids; 75%), while only two plasmids outside ST1 carry bla NDM (one each from ST3 and ST6). Comparison of the bla NDM genetic location has shown multiple genetic organizations (41)(42)(43)(44)(45)(46). Within our database, we observed a total of seven distinct bla NDM structures (see Fig.…”
Section: Figmentioning
confidence: 72%
“…New subtypes, with similar structure, of the gene have been described (fosA2, fosA3, fosA4, and fosA5) (108)(109)(110). Cooccurrence in plasmids with bla CTX-M , bla NDM , bla KPC , bla OXA , bla CMY , bla AmpC , bla TEM , bla SHV , bla SFO-1 , gyrA, parC, parE, sul1, sul2, strA, strB, aac(6=)-Ib, aadA5, aphA6, tetA(A), mphA, floR, dfrA7, rmtB, and merA genes has been reported, conferring resistance to ␤-lactams, quinolones, aminoglycosides, macrolides, sulfonamides, and tetracyclines (75,80,(111)(112)(113)(114). The genes conferring resistance to fosfomycin could be transferred together with genes conferring resistance to other antibiotics in either the same or a conjugate plasmid (114).…”
Section: Acquired Resistancementioning
confidence: 99%
“…Finally, the mutations described above can be found in chromosomes, but the emergence of resistant loci in plasmids (FosA and FosB) could potentially provide a better means for the spread of resistance mechanisms than the chromosomal ones (126). Several recently published studies have shown dissemination of fosfomycin-resistant strains (mainly due to the presence of FosA) in patients as well environmental reservoirs in livestock and animals (75,113,127,128).…”
Section: In Vitro and In Vivo Development Of Resistance And Spreadmentioning
confidence: 99%